PENGEMBANGAN E-LKPD DENGAN PROBLEM BASED LEARNING PADA SUBTEMA MANUSIA DAN LINGKUNGAN BERBASIS LIVEWORKSHEET - Irvan Permana; Rukmini Handayani; Riska Arianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is aim the lack of availability of teaching materials that suit the needs of students, namely variations in teaching materials used for online learning are needed, to find out the activeness and problem-solving solutions of students in learning, be it individuals or groups. This study aims to determine the feasibility and response of students to the developed E-LKPD. The method used is Research and Development (R&D) with ADDIE development. The subjects of this study were students of class V at SDN Pabuaran Cilendek. The data collection instrument used was a validation questionnaire given to 6 validators, 2 media experts, 2 language experts, 2 material experts and student response questionnaires. Validation results by experts obtained the feasibility of E-LKPD with Problem Based Learning, namely the average acquisition from media experts was 90.5%, with the Valid category, the average acquisition from language experts was 97% with the Valid category and the average acquisition from material experts 92% with the Valid category. The results of student responses to E-LKPD with Problem Based Learning obtained a percentage of 97.02% in the Valid category. Based on the results of the overall data analysis, it can be concluded that the E-LKPD with the Liveworksheet-based Problem Based Learning developed is stated to be valid and can be used in thematic learning. Keywords: E-LKPD, Problem Based Learning Liveworksheet.